Columns as an architectural element in theatrical scenery design (Journal of the College of Basic Education, 2022)
The column is an important architectural element with which ceilings or walls are supported, and it is made of stone or wood, and it may be made of metal, as in modern architecture. For both, or according to the artistic style that prevailed in that era, and it differed even in the type of decoration, geometric, plant, or animal. To mention these types and according to historical times.